I Will If You Will: Similarity in Married Partners' Readiness to Change Health Risk Behaviors - Franks, M.; Shields, C.; Lim, E.; Sands, L.; Mobley, S.; Boushey, Carol (Sage Publications, 2012)
Married men and women (N = 1,899 couples) reported readiness to eat a healthier diet, lose weight, and get more exercise (stage of change) and indicated whether they were confident to make these changes (self-efficacy). Husbands' and wives' reports of readiness to change each health behavior were positively associated. Furthermore, women who indicated readiness to eat a healthier diet and get more exercise (contemplation or preparation stages) were less likely to endorse confidence to change when their husbands were in a lower stage than they were relative to those whose husbands shared the same stage of change. Similarly, men who indicated readiness to lose weight were less likely to endorse being confident in their ability to lose weight when their wives were in a lower stage than they were relative to those who shared the same stage. Consideration of interpersonal factors in the behavior change process may enhance behavioral interventions that include married partners together rather than either individual alone.